CARCASS YIELD OF BROILER CHICKENS FED BANANA (Musa paradisiaca) LEAVES FERMENTED WITH Trichoderma viride - Mandey, J. S.; Leke, J. R.; Kaunang, W. B.; Kowel, Y. H. S. (Journal of the Indonesian Tropical Animal Agriculture, 2015)
The study was conducted to evaluate the effect of level of banana (Musa paradisiaca) leaves fermented with Trichoderma viride at different days on the carcass yield of broiler chickens. A hundred and eighty 3-weeks-old broiler chicks were used in this present experiment based on factorial design (3×4). The birds were randomly allocated into three experimental diets containing of 5, 10 and 15% of banana leaves fermented within 0, 5, 10 and 15 days. Each treatment was divided into three replicates of five chicks in each. The experiment was terminated after 4 weeks or when the birds were 7-weeks-old. Feed intake, body weight gain, feed efficiency and carcass yield were measured during the study. The data were subjected to the analysis of variance test followed by least significant difference (LSD) test. Results showed that daily feed intake was significantly affected (P˂0.01) by the dietary treatments, in which feed intake was highest in broilers fed diet containing 10% banana leaves fermented for 10 days. The daily weight gain, feed efficiency and carcass yield were significantly affected (P˂0.01) by the treatments, in which the highest values of daily weight gain, feed efficiency, and carcass yield were observed in birds fed diet containing 10% banana leaves fermented for 10 days. It can be concluded that diet containing 10% banana leaves fermented for 10 days can be included in broiler ration without detrimental effects on the performance and carcass yield.